A Millimeter Wave based Circular Slot Loaded Microstrip Patch Antenna for 5G Communication. (October 2019) - Karthikeyan, V.; Vignesh, S.; Ayyavar Reddy, K.; Bhargavi Reddy, G.; Aparna Sekhar, R. S.
Abstract: This paper presents a microstrip patch antenna for 5G communication at the frequency range of 32GHz. The patch is loaded with multiple circular slots to improve the performance of the antenna. It consists of RT duroid substrate with low dielectric loss tangent 0.0009, dielectric constant 2.2 and thickness 0.5mm, PEC ground and PEC patch. Four various patch antenna with slot array based antenna has simulated on Ansoft HFSS (High Frequency Structural Simulator) Platform. The overall dimensions of designed antennas are 6mm x 6mm x 0.5mm. The performance of antenna is analysed by using simulated results of reflection coefficient, VSWR, gain, bandwidth and directivity and antenna parameters are compared with four antennas. The proposed antennas of reflection co-efficient characteristics is below -10dB at the resonance frequency.